O álcool cinâmico reduz a excitotoxicidade, o estresse oxidativo e a neuroinflamação em camundongos submetidos a modelos de crises epilépticas induzidas por pentilenotetrazol - Monteiro, Álefe Brito (2021)
Cinnamic alcohol (CA) is a phenylpropanoid found in the essential oil of the bark of species of the genus Cinnamomum spp. Schaeff. (Lauraceae Juss.), popularly known as cinnamon. The aim was to evaluate the antiepileptic and neuroprotective effect of CA and its possible mechanisms of action in mice submitted to a pentylenetetrazole (PTZ) induced epileptic seizure models. Swiss male mice were pre-treated with CA (0.3 - 25 mg/kg, ip) and, 60 minutes later, each animal received PTZ (80 mg/kg or 30 mg/kg, ip) to induce acute and chemical kindling models, respectively. In the acute model, the behavioral parameters analyzed were: latency for the first generalized tonic-clonic epileptic seizure (LC), intensity of the first seizure (IC) and latency for death (LM). In turn, in the chemical kindling model, the latency for the first focal bilateral tonic-clonic epileptic seizure (LCF) was recorded for 21 days. Flumazenil antagonism test, neurochemical (malondialdehyde - MDA, nitrite and reduced glutathione - GSH) and histomorphometric tests were performed to investigate the CA mechanism of action in samples of the hippocampus of mice submitted to the acute model. Treatment with CA increased the LC (up to 81.7%) and the LM (82.7%), but without changing the IC in relation to the vehicle group. Pretreatment with flumazenil partially reversed the effects of CA compared to LC (76.0%) and LM (86.4%). The neurochemical analyzes indicated that the CA reduced the concentration of TBARS (34.8%) and nitrite (46.3%) and increased the concentration of GSH (50.5%). Histomorphometric analyzes showed a reduction in inflammation and an increase in neuronal preservation (22.7%) in the hippocampus of mice pretreated with CA and submitted to the acute model. The results of the chemical kindling model, also, showed significant protection registered by the increase in LCF (33.9 - 47.3%) in relation to the vehicle group. Therefore, the possible mechanisms involved in the antiepileptic and neuroprotective activity of CA involve, at least in part, the interaction with the GABAA receptor and decreased excitotoxicity, reduction oxidative stress and the neuroinflammatory process. The findings of this study indicate that CA is a compound with pharmacological effects on the central nervous system, with a potential neuroprotective effect against neurodegenerative diseases, such as epilepsy.